Analysis Efficiency Calculation on Boiler Using Direct (Input-Output) Method in Petrochemical Industry - Diyajeng Luluk Karlina (CV. AFDIFAL MAJU BERKAH, 2025)
The industrial world, particularly the petrochemical industry, is currently experiencing significant growth and advancement. With this rapid development, companies need to pay close attention to the equipment used in the production process, one of which is the boiler. Boiler is one of the main components in the petrochemical plant, as it serves as the equipment responsible for generating steam. Over time, the boiler’s performance will naturally decline due to continuous operation. Therefore, it is necessary to apply a method to evaluate the boiler’s performance. The performance of a boiler is represented by its efficiency value. This value is essential to determine how effectively the boiler produces steam. The higher the efficiency, the better the boiler’s performance. The boiler at the petrochemical plant under study is of the fire tube type. The boiler efficiency analysis in this study was carried out using the input-output method, also known as the direct method. The analysis was performed by comparing the energy obtained from the working fluid (water and steam) with the energy contained in the boiler fuel, represented by the Gross Calorific Value (GCV). Based on the analysis, the highest boiler efficiency was obtained on August 11, 2025, at 65.326858%, due to the high steam temperature of 224.0875°C. Meanwhile, the lowest efficiency was recorded on August 8, 2025, at 45.810117%, which occurred because the boiler had just restarted after a seven-day shutdown.